Disaster types in Malaysia: an overview - Shaluf, Ibrahim Mohamed; Ahmadun, Fakhru'l-Razi (2006)
Purpose: To provide graduate students, researchers, and responsible personnel with an overview on the disaster types worldwide in general and disaster types in Malaysia. Design/methodology/approach: The types of disasters by region for the period 1988-1997 were obtained from recent published sources. The disasters which occurred in Malaysia have been collected from several sources such as the technical, general articles, internet web sites, and internal reports. The disasters which occurred during the period of 1968-2004 have been reviewed. The disasters have been classified into natural disasters, man-made disasters, and subsequent disasters. The man-made disasters have been classified into technological disasters, transportation accidents, public places failure, and production failure. Findings: Disasters have been classified into natural, man-made disasters. The regions worldwide have experienced all kinds of natural disasters in last decade. It was pointed out that the occurrence of disasters from almost all kinds of hazards is among the highest in Asia and the Pacific. Malaysia experienced natural, man-made and subsequent disasters. Malaysia has experienced 39 disasters during the period of 1968-2004. The natural disasters were 49 percent of total disasters. Most of the natural disasters were resulted from the heavy rains. Malaysia has experienced 18 man-made disasters. The man-made disasters resulted in 282 fatalities, and 1,892 injuries. Originality/value: This paper presents an overview on the disaster types by region worldwide. The paper also presents an overview on the disaster types in Malaysia. This paper combined the scattered disasters into one record. Therefore, there is a need for an authorized body to be responsible for the collecting, arranging, classifying, and storing of all type of the accidents in Malaysia. This experience can be benefited from/at any country. © Emerald Group Publishing Limited.